2020
DOI: 10.3390/vetsci7010033
|View full text |Cite
|
Sign up to set email alerts
|

Australian Veterinarians’ Perceptions Regarding the Zoonotic Potential of Mycobacterium avium Subspecies Paratuberculosis

Abstract: Public concerns over exposure to Mycobacterium avium subspecies paratuberculosis (MAP) or MAP components via foods of animal origin could have negative trade consequences, despite the absence of conclusive scientific evidence of a causal association between Mycobacterium avium subspecies paratuberculosis (MAP) and Crohn’s disease (CD). This study was conducted among Australian veterinarians to understand (a) their perceptions regarding the role of MAP in the causation of CD (an ordinal outcome), and (b) their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…It is difficult to compare this response rate to surveys of a similar nature in veterinarians globally or within Australia as many surveys conducted on veterinarians are unable to identify a denominator to calculate a response rate. 35 , 49 , 50 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is difficult to compare this response rate to surveys of a similar nature in veterinarians globally or within Australia as many surveys conducted on veterinarians are unable to identify a denominator to calculate a response rate. 35 , 49 , 50 …”
Section: Discussionmentioning
confidence: 99%
“…46 It is difficult to compare this response rate to surveys of a similar nature in veterinarians globally or within Australia as many surveys conducted on veterinarians are unable to identify a denominator to calculate a response rate. 35,49,50 This survey recorded a low response rate from rural veterinarians (0.8%). Possible reasons include a higher workload for rural veterinarians in some regions, due to a shortage of veterinarians in rural and remote areas.…”
Section: Vaccinationmentioning
confidence: 97%
“…A study conducted among Australian veterinarians regarding their perceptions of the MAP /Crohn’s causation debate revealed that nearly one third viewed MAP as the likely cause of Crohn’s disease and the other two thirds agreed with the adoption of the precautionary principle (Acharya et al 2020 ). The precautionary principal discussions have been entrenched around MAP zoonosis and Crohn’s disease.…”
Section: Parsimonymentioning
confidence: 99%